Friendship and money, oil and water? Credit constraints and "Family and Friends" finance - Manuel Wiegand (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2015)
The use of informal finance is primarily discussed in the context of developing countries and start-up businesses. Survey data used in this study, however, shows that ``Family and Friends'' (F&F) finance is also remarkably widespread among established firms in Germany, a highly developed country. Establishing a causal link, Instrumental Variables estimations in this study show that firms use F&F finance in response to credit constraints. Considering that welfare gains from financial intermediation no longer materialize when firms go informal, this result is of utmost importance in the analysis of the consequences of a non-functioning financial system, even in developed economies.
Keywords: G21; G23; C13; 330